Can Economic Model Transparency Improve Provider Interpretation of Cost-Effectiveness Analysis? A Response. - Cohen, Joshua T.; Wong, John B. (Medical Care, 2017)
To enhance the credibility and the value of health economic analyses, we argue that the computer model source code underlying these analyses should be made publicly available. Only with open publication is it possible for others to assess whether alternative assumptions, beyond those examined by the model authors, alter the model's findings. Because reproducibility is critical for scientific acceptance and because computation increasingly permeates scientific inquiry, other fields have moved toward open publication of computer models, and health economics should avoid falling behind. Making source code available shines a light on these otherwise black boxes and facilitates their complete evaluation and understandability. The preceding commentary makes 2 arguments against open publication. It claims first that open publication would undermine intellectual property rights and discourage work in this field. We respond that the impact on intellectual property would be minimal, and that open publication could even increase model value. The second argument against open publication is the possibility of model misuse. If anything, however, open publication would reduce this risk by making the model implementation completely transparent. We argue finally that open publication of models would have ancillary benefits by making the research more amenable for adaptation and innovation. Moving toward open publication will present challenges, but we believe that the benefits of increased scientific credibility and utility, particularly for health policy and clinical practice decisions, will certainly outweigh the harms.